Fichte's economic philosophy and the current debate concerning distributive justice - Merle, Jean-Christophe (Daimon Revista Internacional de Filosofia, 1994)
It is nevcrlheless truc that Fichtc is the first to have introduced the double synthesis I have emphasized, that is to say, the synthesis of right and progress and that of the individual and the community. In this he was innovative both compared to the egalitarian currents of his period and in comparison with a long, later tradition. He defends an egalitarianism that neither rejects efficiency and progress nor, on the other hand, private properly, the liberty of the individual and the differences demanded by progress. Nevertheless his philosophy still remains a path of originality for the contemporary approach of political philosophy. He does not aim at a fixed, final result but at equality at the outset and genuine competition, and thus he stands in opposition to Rawls, taking into account the criticisms of Sen. He thereby avoids the snags of the notion of the Welfare State and those of conservative liberalism. Lastly and above all, his is not a moral finality of the economy, perfect in the Rawlsian sense. Despite what seem to me to be the legitimate fears that The closed commercial state arouses, I maintain that Fichte corrected the direction of his thinking in The Doctrine of Right of 1812. He clearly expressed his devotion to what constitutes a sine qua non condition of our modernity, by which I do not only mean religious liberly and freedom of thought, but also the liberty of personal aims. Fichte, without renouncing the dimension of religion and community, chose, in all clarity, a form of economic organization that was judicial and secularized.